ANALYSIS OF THE CHARACTERISTICS OF PHYSICAL DEVELOPMENT OF FEMALE VOLLEYBALL PLAYERS - R. Arsova (Trakia Journal of Sciences)
Discovering and selecting sports talents in volleyball is the main and most difficult task for specialists in this sport. In the initial selection, and then in monitoring the physical and technical development of the athletes, coaches rely on the morphoanthropometric features and indicators characteristic of the model of a highly qualified athlete in volleyball. The rapid pace of development of sport, which is characterized by ever closer specialization in individual sports, requires a deepening of knowledge about the structure of the human body. It is very important that the training work is aimed at individualization of training programs, in accordance with the anthropometric, physiological and psychosocial characteristics of each athlete. The purpose of this study is to develop a characteristic description of the state of anthropometric data of 15-18 year old female volleyball players. The analysis on the established average values and variability of the indicators for anthropometry characterizes the studied group as homogeneous. Minor differences are the reason for some sign dissipation in the indicators "Weight" and "Thigh circumference". The characteristic level of the female players is at a satisfactory level compared to the anthropometric criteria in volleyball.